A new stenothoid (Crustacea: Amphipoda: Stenothoidae) from a shallow water hydroid polyp in British Columbia, Canada - Anne Helene S. Tandberg; Wim Vader (Records of the Australian Museum, 2023)
A new stenothoid species is described from a hydroid polyp in British Columbia, Canada. The new species is provisionally assigned to Metopa as M. insolita sp. nov., pending revision of this genus.